The Applicability of The Pecking Order Theory in The Digital Economy - Cui, Yuqi (Transactions on Economics, Business and Management Research, 2024)
The Peck Order Theory (POT), proposed by Myers and Majluf in 1984, posits that firms prioritize their sources of financing based on the principle of least resistance, starting with internal financing, followed by debt, and ending with equity as a last resort. In the context of the digital economy—which is defined by new finance mechanisms and technical advancements like big data, blockchain, crowdsourcing, and artificial intelligence (AI)—this study investigates the applicability and relevance of POT. This study investigates how these contemporary tools impact conventional financing behaviors and preferences through an extensive literature review.The findings suggest that while POT remains a powerful framework, its application in the digital age needs to be modified to account for the reduced information asymmetry and increased efficiency brought about by digital innovations.